Neurosurgery as an opportunity to correct symptoms of mental and behavioural disorders - V. V. Krylov; V. A. Rak (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
Neurosurgical treatment for psychiatric disorders has a controversial history. This branch of neurosurgery called by developer of prefrontal leucotomy and Nobel prize laureate Egaz Moniz “psychosurgery”, was initially based not on scientific researches, but on enthusiasm of individuals and pressing social need. The outcome of psychosurgery regardless of its clinical benefits was the negative attitude of the broad masses and medical community, some countries have banned psychosurgery – the era of psychopharmacology has come. However, some patients suffering from severe course of the psychiatric disorder are resistant to conservative treatment.Over the last decades, the novel neuroimaging methods and neurobiological researches have considerably improved understanding of the pathogenesis of psychiatric disorders and scientific validity of the surgical intervention into the neural circuits. In this article, the main stages of the history of the psychiatric neurosurgery are briefly reviewed. Furthermore, the clinical and surgical considerations including the anatomic target localization, outcome and possible complications of the major operations which are still in practice are presented. The new neurosurgical techniques such as deep brain stimulation and gamma knife stereotactic radiosurgery were also considered. The part of the article is devoted to ethical, legal and terminological issues of psychiatric neurosurgery.